Clinical recommendations for defining platinum unsuitable head and neck cancer patient populations on chemoradiotherapy: A literature review. (February 2016) - Ahn, Myung-Ju; D'Cruz, Anil; Vermorken, Jan B.; Chen, Jo-Pai; Chitapanarux, Imjai; Dang, Huy Quoc Thinh; Guminski, Alex; Kannarunimit, Danita; Lin, Tong-Yu; Ng, Wai Tong; Park, Keon-Uk; Chan, Anthony Tak Cheung
Highlights: Platinum-based CCRT, as a standard form of treatment in LA-SCCHN, is hampered by toxic effects. Knowledge gaps exist in criteria for platinum unsuitability with LA SCCHN. We try to identify patients who are ineligible for platinum based therapy or at high risk of severe toxicities. Age, co-morbidity and organ dysfunctions are the most important factors that need to be considered. Alternative options are available; but there has been no sufficient evidence to support these approaches in reaching the same level of recommendation. Summary: Toxicities resulting from platinum based chemotherapy in head and neck cancer is a cause for much concern. There is a lack of clinical criteria for defining these patient populations, which has posed serious problems associated with increased morbidity and consequently an adverse effect on patients' quality of life. In addition, there is a lack of consensus on clinical criteria for defining such patient populations, who may be unsuitable for concurrent chemoradiotherapy. A group of experts in the field of head and neck cancer from the Asia Pacific Region convened in August 2014 in Korea to discuss the development of a set of clinical criteria in order to fill the knowledge gap and provide a reference tool for head and neck oncologists. This paper reports the final output from this meeting and the accompanying literature review, with the aim of aiding clinical decision making with the help of some clinical criteria to identify platinum unsuitable patient populations in head and neck cancer management. Some alternative treatment options are also discussed in this paper.